PENGATURAN TENTANG PENYADAPAN (INTERSEPSI) DALAM PERUNDANG-UNDANGAN DI INDONESIA - Adhy Iswara Sinaga; Madiasa Ablisar; Mahmud Mulyadi; Suhaidi Suhaidi (USU LAW JOURNAL, 2015)
ABSTRACT The arrangement of tapping in national legislation is arranged differently, some of them are arranged in details and some of them are not. Each of the arrangement is different depending on the needs on the institution and the needs of each institution. None of the act can be used as common guideline. The importance of tapping regulation should be made in a form of act because it connects with Human Rights and based on the constitution, Human Rights can only restricts through the act, not Government Regulation. The authority for taping which law enforcement normatively has cannot be contrary to Human Rights, after all the restriction of Human Rights is matched by the nature of Criminal Law itself which to limit every individual freedom that allowed by the law. The Government and Legislatives should make an act as a common guideline which regulates tapping. So the House of Representatives and the President can outsmart and dig deeper into the importance of tapping made into an act, not into a Government Regulation. Everybody should distinguish intelligently and carefully to indicate tapping as a violation of Human Rights. The mechanism of tapping should be regulated as clearly, firmly, and directed as possible. An exception can be necessary in order to avoid any violation of Human Rights. Keyword: Legislation, Tapping, and Human Rights.